Encouraging general practitioners to complete the four‐year‐old Healthy Kids Check and provide healthy eating and physical activity messages. (22nd April 2014) - Bell, A. Colin; Campbell, Elizabeth; Francis, J. Lynn; Wiggers, John
Abstract Objective: To describe the impact of a training and support intervention to encourage completion of the Healthy Kids Check (HKC) by general practitioners (GP) or practice nurses (PN) and provision of brief advice on diet and physical activity. Methods: The intervention (June 2008 to July 2010) was delivered by Divisions of General Practice (DGP) in the Hunter New England (HNE) region of NSW, Australia, to members in 300 practices. Intervention impact was evaluated using Medicare data on the number of HKCs completed and a post‐intervention telephone survey of randomly selected parents in HNE and rest of NSW. Results: Training reached 31% of GPs (n∼ 216/700) and 71% of PNs (n∼320/450); 31% of four‐year‐olds received a HKC in HNE compared to 15% in NSW; 27% of HNE parents (n=162) reported a GP or PN had provided advice during their child's vaccinations visit compared to 15% of parents (n=154) in NSW (p=0.002). There was no significant difference in proportion of children who had weight or height assessed (55.6% in HNE and 54.6% in NSW). Conclusions: Boosting HKC claims and healthy eating and physical activity messages in general practice is feasible. More intensive strategies are required if obesity prevention and management benefits are to be achieved. Implications: General practice is an important but under‐utilised source of advice for parents and data for policy makers on childhood obesity in Australia.